HDAC7: a promising target in cancer - Liu, Cui; Zheng, Dan; Pu, Xuan; Li, Sijun (Frontiers in Oncology, 2024)
Histones have a vital function as components of nucleosomes, which serve as the fundamental building blocks of chromatin. Histone deacetylases (HDACs), which target histones, suppress gene transcription by compacting chromatin. This implies that HDACs have a strong connection to the suppression of gene transcription. Histone deacetylase 7 (HDAC7), a member of the histone deacetylase family, may participate in multiple cellular pathophysiological processes and activate relevant signaling pathways to facilitate the progression of different tumors by exerting deacetylation. In recent years, HDAC7 has been increasingly studied in the pathogenesis of tumors. Studies that are pertinent have indicated that it has a significant impact on the growth and metastasis of tumors, the formation of the vascular microenvironment, and the emergence of resistance to drugs. Therefore, HDAC7 could potentially function as a potent predictor for tumor prognosis and a promising target for mitigating drug resistance in tumors. This review primarily concentrates on elucidating the structure and function of HDAC7, its involvement in the development of various tumors, and its interplay with relevant signaling pathways. Meanwhile, we briefly discuss the research direction and prospect of HDAC7.